Surveying the avant-garde : questions on modernism, art, and the Americas in transatlantic magazines - Cole, Lori, 1980- (Refiguring modernism., 2018)
"Examines art and literature of the Americas through the lens of the questionnaire, a genre as central as the manifesto to the history of the avant-garde. Demonstrates how modernism and the avant-garde were debated at the very moment of their development and consolidation"--Provided by publisher